Frequency of Metabolic Syndrome in Patients with Chronic Plaque Psoriasis - Sadaf Sabir, Saima Ilyas, Mehwish Khan, Hina Imtiaz, Eraj Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To know the frequency of occurrence of metabolic syndrome in patients suffering from chronic plaque psoriasis. Methods: This cross-sectional study was done in dermatology outpatient clinic of tertiary care hospital Faisalabad. Sample size of the study was 125 patients from population of Faisalabad. For enrolling patients in our study consecutive sampling method was used. After seeking approval from ethical hospital committee and completing inclusion and exclusion criteria, a total 125 patients of both gender having plaque psoriasis (between ages of 20-60 years) were taken in this study. Demographic details were noted. A fasting venous blood sample was taken and delivered to hospital laboratory for accessing triglycerides, HDL and fasting blood glucose levels. Waist circumference and blood pressure reading was taken by staff nurse. All the data was recorded on self-made performa. Results: Out of 125 patients, 71(56.8%) were male and 54(43.2%) were females; 31 (24.8%) were in the range of 20-30 years of age whereas 94(75.2%) were in the range of 31-60 years. Mean +Standard Deviation was measured as 37.96+8.05 years. Out of 125 psoriatic patients, the frequency of metabolic syndrome was seen in 37 (29.6%) of cases. Practical Implication: The connections between MS and psoriasis provide psoriasis patients with early possibilities for MS diagnosis and treatment, which could result in a significant decrease in morbidity and mortality. Different geographic regions and ethnic groups show significant differences in the symptoms of psoriasis and metabolic disorders. It can aid in the prevention and treatment of metabolic syndrome-related complications. Conclusion: Because of significant relationship of metabolic syndrome with chronic plaque psoriasis, all psoriatic patients must be tested for metabolic syndrome and thus managed according to fasting lipid profile levels to decrease the incidence of cardiovascular morbidity and mortality Keywords: chronic plaque psoriasis, metabolic syndrome, dermatology, triglycerides, waist circumference